Analysis of corporate sustainability performance and corporate financial performance causal linkage in the Indian context - Milind Kumar Jha; K. Rangarajan (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2020)
This paper aims to explore the relationship between corporate sustainability performance (CSP) and corporate firm performance (CFP) for a sample of the top 500 Indian firms covering the period from 2008 to 2018. CSP variables have been considered at both aggregate and disaggregate levels of environmental, social and governance performance. CFP has been evaluated in both accounting and marketbased measures. Rigorous statistical methods have been used to evaluate the bidirectional causality and intensity of the CSP-CFP relationship using the Granger causality test and multiple regression for panel data. A sectoral level trend analysis is presented dividing the firms in various industries and classifying them in ESI vs non-ESI sectors. The findings indicate the absence of causality among CSP and CFP variables in either direction and suggest that the CSP-CFP linkage is mostly insignificant for Indian firms at the aggregate level. At an individual level, some negative association is found between CSP and CFP. This relationship has an adverse impact on CSP-CFP linkage in both cases, which means that Indian firms don't get the financial performance benefits of investments done for sustainability. Our findings with mostly insignificant results for this relation also means that firms with higher or lower CSP on ESG dimensions will perform likewise in terms of CFP. The findings have practical implications for corporates, academicians, and policymakers alike given sustainability as a high focus area for all.
Keywords: 650; Corporate sustainability performance; Corporate financial performance; ESG; Indian firms; CSP; CFP; Granger causality